Integrated Management Practices for Establishing Upland Switchgrass Varieties - Pawan Kumar; Masoud Hashemi; Stephen J. Herbert; Emad Jahanzad; Hadi Safari-Katesari; Martin Battaglia; Omid Reza Zandvakili; Amir Sadeghpour (Agronomy, 2021)
Establishment of switchgrass (Panicum virgatum L.) is challenging, and failure in establishment may expose growers to considerable economic risk. The objectives of this research were to (i) evaluate whether management practices are variety-specific for the establishment of switchgrass and (ii) assess the effectiveness of cover crops as preceding crops on ‘Shawnee’ switchgrass establishment. Therefore, two studies were conducted at the University of Massachusetts Agricultural Experiment Station in Deerfield, MA, USA, in the 2011–2012 and 2012–2013 growing seasons. In Experiment 1, cover crop treatments (fallow, oat (Avena sativa L.) and rye (Secale cereale L.)) were the main plots, the two seeding methods (no-till drill and a cultipacker seeder (Brillion)) were the sub-plots, and the two varieties (‘Cave-in-Rock’ (CIR) and Shawnee)) were the sub-sub-plots. The second study was conducted using Shawnee switchgrass and involved the three cover crop treatments used in Experiment 1 using a cultipacker seeder with seed firming prior to planting but not afterwards (consistent in both experiments). The results indicated that a combination of oat and no-till resulted in higher tiller density (493%), lower weed biomass (77%), increased switchgrass biomass (SGB) (283%) and SGB to weed biomass (WB) ratio. Compared with Shawnee, CIR planted into a winter-killed oat residue had higher tiller density (93%), lower weed biomass (18%), higher switchgrass yield (128%) and thus a greater SGB:WB ratio (507%). Trends of switchgrass response to management practices, however, were similar between the two varieties, indicating that seed quality rather than management practices could influence switchgrass’s response to management practices. In Experiment 2, Shawnee tiller density was suppressed by rye as the preceding crop, possibly due to late termination of rye. Shawnee switchgrass yields were below 1000 kg ha−1 under all management practices; thus, harvesting should happen in the year following establishment. Future research should focus on comparing no-till drilling with cultipacker seeder with rolling not only before but after seeding to increase seed–soil contact.